2013
DOI: 10.1016/j.jpowsour.2013.05.149
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization and elementary reaction modeling of solid oxide electrolyte direct carbon fuel cell

Abstract: A detailed mechanistic model for solid oxide electrolyte direct carbon fuel cell (SO-DCFC) is developed while considering the thermo-chemical and electrochemical elementary reactions in both the carbon bed and the SOFC, as well as the meso-scale transport processes within the carbon bed and the SOFC electrode porous structures. The model is validated using data from a fixed bed carbon gasification experiment and the SO-DCFC performance testing experiments carried out using different carrier gases and * Corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…On the other hand, it suffers from low power density, which must be increased to make it commercially viable. In a DC-SOFC [9,10], carbon can be electrochemically oxidized directly to CO 2 according to Eq. 1:…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it suffers from low power density, which must be increased to make it commercially viable. In a DC-SOFC [9,10], carbon can be electrochemically oxidized directly to CO 2 according to Eq. 1:…”
Section: Introductionmentioning
confidence: 99%
“…In the case depicted in Figure 1, the electrochemical oxidation of carbon particles mainly occurs according to reaction (1) [27,28]. The current and power generated from DC-SOFC (1) could be directly addressed to direct carbon oxidation according to reaction (1), making it easily possible to determine the activity of solid particles in the anode reaction of the direct electrochemical oxidation of fuel.…”
Section: Methodsmentioning
confidence: 99%
“…49carbon fuel cells have been operated on a wide range of fuels including coal, liquid hydrocarbon fuels, biomass and organic waste. Some of these fuels have been used directly within the fuel cell with very little pre-treatment whilst others have been heavily processed and purified to produce a fuel that is almost pure carbon [34]. Dudek et al [35] have reported an investigation of various types of carbon blacks and have tried to correlate their electrochemical reactivity in a molten carbonate electrolyte based DCFC with micro-and nanostructures of carbons, which shows in Fig.…”
Section: R E T R a C T E D R E T R A C T E D R E T R A C T E D R E T mentioning
confidence: 99%